The Role of Government in Restoring International Competitiveness: the Case of Crisis Management in the Baltic States Economies versus Poland Economies - Matysek-J?drych, Anna (Journal of Eastern European and Central Asian Research (JEECAR), 2014)
<!--[if gte mso 9]> <![endif]-->This paper focuses on the relationship between the government actions, global economic crisis, and competitiveness on a national and regional dimension. The Baltic States (i.e., Estonia, Latvia, and Lithuania) have experienced one of the biggest Gross Domestic Product (GDP) contractions during the Global Crisis so far. Meanwhile, Poland was the only country with a positive GDP growth in the European Union during the Global Crisis. Hence, identifying and assessing changes in the relative competitiveness, as a consequence of the economic downturn in both Baltic States and Poland, has sparked many interests. The main channel through which the crisis undermined competitiveness has been the macroeconomic situation. That is why employing single macroeconomic variables as proxies of competitiveness suggests a much stronger influence of the crisis on competitiveness in comparison to overall measures (e.g. Global Competitiveness Index). It may be generally concluded that a short-term crisis, even if severe, does not have a negative influence on international competitiveness as long as a proper anti-crisis policy is implemented and the country is small enough to react fast and adapt to new conditions in the global environment.